656 Cough, a rare and not well recognized symptom of lead perforation. (8th December 2021) - Parisi, Francesca; Demurtas, Elisabetta; Allegra, Marta; Pistelli, Lorenzo; Frecentese, Francesca; Dattilo, Giuseppe; Luzza, Francesco; Carerj, Scipione; Crea, Pasquale; Micari, Antonio; Di Bella, Gianluca
Abstract: Aims: Along with relevant progress in technology, pacemaker implantation is continuously improving its safety and efficacy in treating patients with bradyarrhythmias. Despite this, this procedure has several complications, including haematoma, pneumothorax, lead dislodgement, infection, lead perforation, and tamponade. Methods and results: A 64-year-old woman underwent loop recorder implantation, after recurrent loss of consciousness, in order to assess arrhythmic causes of syncope. Two weeks later, an episode of paroxysmal complete AV block, conditioning a pause of 3 s, was recorded. Thus, the patient was scheduled for urgent dual-chamber pacemaker implantation. No complication apparently occurred during the procedure. An active fixation ventricular lead was positioned in right ventricular septal apex while passive fixation atrium lead in the right appendage. Soon after implantation the patient started to suffer by non-productive cough, clearly related to ventricular stimulation, either in DDD or in VVI pacing modality. During spontaneous ventricular activation (RBBB) no symptoms occurred. Transthoracic echocardiography, performed the day after implantation, revealed a small pericardial effusion (diastolic diameter < 10 mm) along the apical segments, near the tip of the right ventricular lead. Suspicion of right ventricular lead perforation arised. The patient underwent urgent contrast chest CT confirming pericardial effusion, and showing an intramyocardium placement of the right ventricular apical lead. No active bleeding in pericardium was observed. Due to persistence of symptoms, we decided to perform right ventricular lead repositioning in right middle septum, with pericardiocentesis back-up promptly available. Post-procedure, palpitation, and cough abruptly disappeared. After 3 months follow-up, no significant symptoms were reported and pericardial effusion gradually disappeared. Conclusions: We describe a singular case of cough, as atypical symptom immediately after pacemaker implantation. Pericardial effusion and contrast-CT showing intra-myocardial position of the tip guided our suspicion to a possible right ventricular lead microperforation. Although right ventricular lead parameters were completely normal this findings didn't exclude RV perforation. The lead perforation is known as a rare complication of device implantation. Typical symptoms of RV lead perforation are chest pain and hypotension. The patient described in our case showed a haemodynamically stable pericardial effusion accompanied by non-productive cough, clearly time-related to RV stimulation. In literature, there is only another similar case report. The cough is a rare and not well recognized symptom of lead perforation. Early diagnosis of RV perforation allows to perform urgently and safely (pericardiocentesis back-up) lead replacement/repositioning. Echocardiography and contrast-CT could be useful in order to assess a possible pericardial effusion or intramyocardial/pericardial position of RV lead tip.